The GDP Impact of Reform A Simple Simulation Framework - Barnes, Sebastian (OECD Economics Department Working Papers, 2013)
This paper presents a framework to assess the impact of a wide range of structural policy reforms on GDP per capita at various horizons by linking together previous empirical studies mostly carried out by the OECD. The simple accounting framework consists of reduced-form equations and offers a more tractable and realistic alternative to an estimated general equilibrium model. Though this involves some risks of double counting the effects of certain reforms and omits interactions across different policy areas, the plausible scenarios suggest that the largest long-run GDP per capita gains may be obtained from reforms that would raise the quantity and quality of education, strengthen competition in product markets, reduce the level and/or duration of unemployment benefits, cut labour tax wedges and relax employment protection legislation. Past reforms in these areas might also have contributed to as much as half of GDP per capita growth in OECD countries in the decade prior to the recent financial and economic crisis. Simulations further indicate that addressing all policy weaknesses in each OECD country by aligning policy settings on the OECD average could raise GDP per capita by as much as 25% in the typical country